Develop Critical Spatial Thinking by Utilizing Local Landscapes: Geography Field Laboratory Studies. Issue 1 (March 2021) - As'ari, R; Maryani, E; Rohmat, D; Nandi
Abstract: Geographical skills that need to be shared by each geographic are three categories, including map skills, field skills, and satellite image interpretation skills. To achieve field skills competency, a location is needed to be used as material for practicum studies for each subject. The Geography Education Field Laboratory can be studied in depth based on an analysis of the level of learning needs. The basis of the lab location requirements as a laboratory is seen from the laboratory function as an area to carry out careful and accurate testing and measurement of the phenomenon under study. Local landscape can be used as a field laboratory to improve critical spatial thinking skills. The study was carried out through the identification of local landscapes by delineating the area through the utilization of satellite imagery and identifying potential from each area that was chosen descriptively. Location characteristics to be used as locations for geography learning resources can describe geographical concepts, local landscapes, and regional phenomena.